Vital signs monitoring system on a smart bed - Huang, Jiachong (2014)
Fiber Bragg grating (FBG) is a longitudinal periodic variation of the index of refraction in the core of an optical fiber. Only certain wavelength (Bragg Wavelength) of light will be reflected if a broad spectrum of light is incident into the FBG. When the FBG encounters strain or temperature change, the Bragg Wavelength will shift accordingly.